The Ideology of Climate Change Denial in the United States - Jean-Daniel Collomb (European Journal of American Studies)
The concerted effort to discredit the scientific consensus over man-made global warming has been continuing for two decades in the United States, and shows no sign of weakening. It is very often described as an attempt on the part of corporate America, most notably the fossil fuel industries, to hinder governmental regulations on their activities. While emphasising this dimension of the US climate denial movement, this article also aims to show the complexity of the movement, rather than the mere defence of the narrowly-defined and short-term economic interests of the oil and gas industries, by shedding light on two additional factors which have been instrumental in blocking strong climate action. First, climate denial stems from the strong ideological commitment of small-government conservatives and libertarians to laisser-faire and their strong opposition to regulation. Second, in order to disarm their opponents, US climate deniers often rest their case on the defence of the American way of life, defined by high consumption and ever-expanding material prosperity. It is the contention of this article, therefore, that the US climate denial movement is best understood as a combination of these three trends.